Research in Musculoskeletal Radiology: Setting Goals and Strategic Directions - Klontzas, Michail E.; Karantanas, Apostolos H. (Seminars in Musculoskeletal Radiology, 2022)
The future of musculoskeletal (MSK) radiology is being built on research developments in the field. Over the past decade, MSK imaging research has been dominated by advancements in molecular imaging biomarkers, artificial intelligence, radiomics, and novel high-resolution equipment. Adequate preparation of trainees and specialists will ensure that current and future leaders will be prepared to embrace and critically appraise technological developments, will be up to date on clinical developments, such as the use of artificial tissues, will define research directions, and will actively participate and lead multidisciplinary research. This review presents an overview of the current MSK research landscape and proposes tangible future goals and strategic directions that will fortify the future of MSK radiology.
Keywords: research; artificial intelligence; biomarkers; musculoskeletal; molecular imaging